1.4 Mb candidate gene region for X linked dyskeratosis congenita defined by combined haplotype and X chromosome inactivation analysis. Issue 12 (December 1998) - Knight, S W; Vulliamy, T J; Heiss, N S; Matthijs, G; Devriendt, K; Connor, J M; D'Urso, M; Poustka, A; Mason, P J; Dokal, I
Abstract : Dyskeratosis congenita (DC) is a rare inherited disorder characterised by the early onset of reticulate skin pigmentation, nail dystrophy, and mucosal leucoplakia. In over 80% of cases bone marrow failure develops and this is the main cause of early mortality. The DC1 gene responsible for the X linked form (MIM 305000) of dyskeratosis congenita has been mapped to Xq28. In order to narrow the candidate gene region, genetic linkage analysis was performed in eight X linked pedigrees using a set of markers spanning Xq28. A maximum lod score of 5.31 with no recombinations was achieved with marker DXS1073. Two recombination events were identified; one of these uses X chromosome inactivation pattern analysis to determine carrier status and haplotype analysis to fine map the recombination breakpoint. The fine mapping of these recombination events has enabled the candidate gene region for X linked dyskeratosis congenita to be defined as the 1.4 Mb interval between Xq3274 and DXS1108.